Comparative drug release kinetics of Terminalia arjuna mediated SeNPs NanoGel and ZnONPs NanoGel – An in-vitro study - R. Vijayalakshmi; N. Ambalavanan; S. Rajeshkumar; Jaideep Mahendra; Uma Sudhakar; Devi Parameswari (Journal of Oral Biology and Craniofacial Research)
Background: This study compared the drug release kinetics of Terminalia arjuna mediated selenium nanoparticles (SeNPs) gel and zinc oxide nanoparticles (ZnONPs) gel for their potential in local drug delivery for chronic periodontitis. Material and method: The drug release was evaluated in-vitro by conducting tests on different formulations, including 1 %, 2 %, 3 %, 4 %, and 5 % Terminalia arjuna mediated SeNPs gel and ZnONPs gel. Each sample, approximately 0.1 mg, was mixed with 10 mL of phosphate buffer saline (PBS) at various pH levels and maintained at 37 °C. The suspension was then placed in an incubated shaker at 120 rpm for 1 h. Five-milliliter samples were withdrawn from the dissolution medium at 30-min intervals and replaced with fresh PBS buffer to maintain a constant volume. The released drug amount was measured using a UV spectrophotometer (Systronics, India) at 290 nm. Result: The investigation revealed that SeNPs gel exhibited higher drug release percentages compared to ZnONPs gel across various concentrations and time points. The sustained release profiles of both formulations suggest effective control over drug release, maintaining therapeutic drug levels over an extended period. The near-complete release of the drug at 500 min highlights the potential for prolonged therapeutic efficacy, reducing the need for frequent dosing and enhancing patient compliance. Conclusion: Terminalia arjuna mediated SeNPs gel shows promise for more rapid and sustained drug delivery in the management of chronic periodontitis through local drug delivery systems.